2016
DOI: 10.1016/j.jddst.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-N-acetyl cysteine microspheres for ocular delivery of acyclovir: Synthesis and in vitro/in vivo evaluation

Abstract: This paper presents the main aspects regarding the production of biodegradable microspheres, the optimization of parameters in the drug encapsulation process, the techniques available for polymeric systems sterilization and the effects of γ-irradiation on microparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 106 publications
1
9
0
Order By: Relevance
“…The shifts in the peak for Amide II in SF NPs from 1537 cm −1 to 1524 cm −1 for SF/NAC NPs were possibly due to the presence of Amide II in NAC (Figure 2). There was a minor peak at 2330 cm −1 for SF/NAC NPs, which was attributed to the SH groups in NAC, as reported by other studies [36].…”
Section: A Analysis Of Atr-ftir Spectra For Examining Functions Group...supporting
confidence: 82%
“…The shifts in the peak for Amide II in SF NPs from 1537 cm −1 to 1524 cm −1 for SF/NAC NPs were possibly due to the presence of Amide II in NAC (Figure 2). There was a minor peak at 2330 cm −1 for SF/NAC NPs, which was attributed to the SH groups in NAC, as reported by other studies [36].…”
Section: A Analysis Of Atr-ftir Spectra For Examining Functions Group...supporting
confidence: 82%
“…The formulations were prepared using emulsification crosslinking process, the microspheres having an active substance incorporation efficiency of 97.86 AE 2.06% for the chitosan microspheres and 76.99 AE 1.14% for the thiolate derivatives. In vitro release studies showed an initial burst followed by a sustained release of acyclovir for 12 h, and in vivo studies did not indicate signs of ocular toxicity [128].…”
Section: Microspheresmentioning
confidence: 90%
“…Rajawat et al reported a thiolated CS derivative, 6 in Scheme 1, as a microcarrier for the ocular delivery of acyclovir [195]. N-Acetylcysteine was covalently bonded to CS via a carbodiimide-mediated coupling reaction.…”
Section: Nanoparticles From Modified Chitosanmentioning
confidence: 99%